Returning to the Flint Hills - John B.T. Campbell III (Symphony in the Flint Hills, 2016)
It was December of 1914. A short four months earlier the fighting in Europe had broken out in the great conflagration that would be known as “the war to end all wars.”
Keywords: Cottonwood Falls; Kansas; George and Myrtle McNee; Los Angeles; technology; natural amphitheater; HORIZON GREEN; Lisa Grossman; C-GREEN; Mariana Escribano